2010
DOI: 10.1177/1059840510391267
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Use of School Health Data

Abstract: Meaningful use (MU) of Electronic Health Records (EHRs) is an important development in the safety and security of health care delivery in the United States. Advancement in the use of EHRs occurred with the passage of the American Recovery and Reinvestment Act of 2009, which provides incentives for providers to support adoption and use of EHRs. School nurses play an important role in alerting the public and key decision makers to the value of school health data to the MU of EHRs. The timeline for adopting MU of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…For example, many indicated that even data collection is done using educational software that may not be conducive to their needs. Emphasis on meaningful use of electronic health care records to improve care is critical in school health (Johnson & Bergren, 2011). To complicate matters, as health care and education reform continues, school nurses are seeing added pressures to their responsibilities.…”
Section: Resultsmentioning
confidence: 99%
“…For example, many indicated that even data collection is done using educational software that may not be conducive to their needs. Emphasis on meaningful use of electronic health care records to improve care is critical in school health (Johnson & Bergren, 2011). To complicate matters, as health care and education reform continues, school nurses are seeing added pressures to their responsibilities.…”
Section: Resultsmentioning
confidence: 99%
“…There is little research regarding the work environment of school nurses' organizational factors that influence work satisfaction. A review of the literature revealed that while school nurses perceive barriers and challenges to professional practice (Combe et al, 2015;Fleming, 2012;Johnson & Bergren, 2011;Krause-Parello & Samms, 2009;Magalnick & Mazyck, 2008;Mangena & Maughan, 2015;Maughan & Mangena, 2014;National Association of School Nurses, 2015), few studies have examined or empirically measured work satisfaction of the school nurse. Understanding factors that influence work satisfaction among school nurses has significant implications because the current health-care delivery system is transitioning from care of the individual with disease to one of disease prevention among populations (Bergren, 2017;Moreland-Russell, Combs, Polk, & Dexter, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, using electronic health information systems to document care improves the efficiency and utility of school health data, allowing it to be used in a meaningful manner to support students (Johnson & Bergren, 2010). Electronic information systems allow a huge volume of data to be entered rapidly, analyzed comprehensively from multiple perspectives, and efficiently reported to key stakeholders.…”
Section: The Value Of Electronic Documentation Systemsmentioning
confidence: 99%